2022
DOI: 10.3389/fmed.2022.840030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Potential Biomarkers for Retinopathy of Prematurity

Abstract: Retinopathy of prematurity (ROP) is the main risk factor for vision-threatening disease in premature infants with low birth weight. An accumulating number of independent studies have focused on ROP pathogenesis and have demonstrated that laser photocoagulation therapy and/or anti-VEGF treatment are effective. However, early diagnosis of ROP is still critical. At present, the main method of ROP screening is based on binocular indirect ophthalmoscopy. However, the judgment of whether ROP occurs and whether treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 136 publications
(154 reference statements)
0
18
0
Order By: Relevance
“…Disruption of the gut microbiota not only causes gastrointestinal diseases but also exerts systemic effects by changing intestinal permeability, releasing metabolic endotoxins into the blood circulation, inducing systemic inflammatory responses, and altering body growth [ 373 , 374 ]. Systemic inflammatory status potentially takes part in the development of diseases in all systems, including ophthalmic disorders [ 375 ]. The concepts of gut–brain [ 373 , 376 ], gut–respiratory [ 376 ], and gut–retina axes [ 374 , 377 ] have been discussed in the literature.…”
Section: Novel Pharmacological Agents Linking To Cytokine Signaling P...mentioning
confidence: 99%
“…Disruption of the gut microbiota not only causes gastrointestinal diseases but also exerts systemic effects by changing intestinal permeability, releasing metabolic endotoxins into the blood circulation, inducing systemic inflammatory responses, and altering body growth [ 373 , 374 ]. Systemic inflammatory status potentially takes part in the development of diseases in all systems, including ophthalmic disorders [ 375 ]. The concepts of gut–brain [ 373 , 376 ], gut–respiratory [ 376 ], and gut–retina axes [ 374 , 377 ] have been discussed in the literature.…”
Section: Novel Pharmacological Agents Linking To Cytokine Signaling P...mentioning
confidence: 99%
“…ROP is a major cause of childhood blindness among infants born preterm. As this condition is frequently misdiagnosed (18), the identification of biomarkers can improve the diagnostic process as well as the assessment of disease prognosis. The original research provided by Li et al revealed that altered expression of circular RNAs-stable noncoding RNAs-in the peripheral blood mononuclear cells may be used as potential biomarkers for treatment-requiring ROP infants.…”
Section: Editorial On the Research Topic State Of The Art In Immunopa...mentioning
confidence: 99%
“…Several biomarkers, such as metabolites, cytokines, growth factors, non-coding RNAs, gut microbiota, or oxidative stress markers, have been proposed for the diagnosis or prediction of ROP [ 13 ]. The role of thrombocyte parameters in the prediction of ROP has been studied in several papers that have outlined the involvement of these elements in neoangiogenesis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%